Chickens fed with different levels of flour Erythrina poeppigiana and flour Trichanthera gigantea (Revista Sistemas de Producción Agroecológicos, 2011)
Two experiments were conducted at the Universidad de los Llanos, Villavicencio (Meta), the main objective was to observe the productive performance of broilers that were given diets with different levels of Trichanthera gigantea flour (TF) and flour Erythrina poeppigiana (EF) (0, 5, 8 and 12%), replacing other sources of protein such as meat meal is traditionally used in poultry diets. The variables studied were: weight gain, consumption, conversion, biological value of protein, coefficient protein efficiency (CPE) and carcass yield. The chickens were distributed in a completely randomized design, consisting of four treatments in experiment one were: control (0% TF), Trichanthera I (5% TF), Trichanthera II (8% TF) III Trichanthera (12% TF), and in experiment two were: control (0%EF), Erythrina I (5% EF), Erythrina II (8% EF) and Erythrina III (12% EF). In the case of TF found that when levels were increased feed intake decreased (P
Keywords: chickens; trees; biological value